Attitudes of women and men living with HIV and their healthcare providers towards pregnancy and abortion by HIV-positive women in Nigeria and Zambia (2015)
Fertility decisions among people living with HIV/AIDS (PLWHA) are complicated by disease progression, the health of their existing children and possible antiretroviral therapy (ART) use, among other factors. Using a sample of HIV-positive women (n = 353) and men (n = 299) from Nigeria and Zambia and their healthcare providers (n = 179), we examined attitudes towards childbearing and abortion by HIV-positive women. To measure childbearing and abortion attitudes, we used individual indicators and a composite measure (an index). Support for an HIV-positive woman to have a child was greatest if she was nulliparous or if her desire to have a child was not conditioned on parity and lowest if she already had an HIV-positive child. Such support was found to be lower among HIV-positive women than among HIV-positive men, both of which were lower than reported support from their healthcare providers. There was wider variation in support for abortion depending on the measure than there was for support for childbearing. Half of all respondents indicated no or low support for abortion on the index measure while between 2 and 4 in 10 respondents were supportive of HIV-positive women being able to terminate a pregnancy. The overall low levels of support for abortion indicate that most respondents did not see HIV as a medical condition which justifies abortion. Respondents in Nigeria and those who live in urban areas were more likely to support HIV-positive women’s childbearing. About a fifth of HIV-positive respondents reported being counselled to end childbearing after their diagnosis. In summary, respondents from both Nigeria and Zambia demonstrate tempered support of (continued) childbearing among HIV-positive women while anti-abortion attitudes remain strong. Access to ART did not impart a strong effect on these attitudes. Therefore, pronatalist attitudes remain in place in the face of HIV infection.